Structural characteristics, antioxidant and hypoglycemic activities of polysaccharides from Mori Fructus based on different extraction methods - Huang, Yuanyuan; Xie, Wen; Tang, Ting; Chen, Huaguo; Zhou, Xin (Frontiers in Nutrition, 2023)
In this study, six mulberry fruit polysaccharide (MFP) fractions were extracted by different extraction methods, and their physicochemical structures, antioxidant, and hypoglycemic biological activities were investigated and compared. The results showed that MFP-III showed the strongest inhibition of ɑ-glucosidase and ɑ-amylase, while MFP-IV showed the strongest scavenging activity against DPPH and ABTS. The results of high-performance liquid chromatography (HPLC) and scanning electron microscopy (SEM) showed that different extraction methods had significant effects on the monosaccharide composition and apparent morphology of MFP. The results of Fourier transform infrared spectroscopy (FT-IR), nuclear magnetic resonance (NMR), thermogravimetric analysis (TG), and Congo red experiments showed that the extraction methods did not differ significantly in terms of functional groups, glycosidic bonds, triple helix structure and thermal stability of MFP. The above results found that different extraction methods had specific effects on the chemical structure and biological activity of mulberry polysaccharides, which can provide a scientific basis for selecting suitable extraction methods to obtain mulberry polysaccharides with ideal biological activity.